A case of Lemierre's syndrome with double vision as the first symptom. Issue 2 (February 2022) - Fukushima, Koki; Takazono, Takahiro; Ashizawa, Nobuyuki; Hara, Shintaro; Kitaoka, Kyoko; Ideguchi, Reiko; Miyazaki, Teiichiro; Hirayama, Tatsuro; Yamamoto, Kazuko; Imamura, Yoshifumi; Miyazaki, Taiga; Izumikawa, Koichi; et al.
Abstract: Lemierre's syndrome is a serious disease that typically causes oropharyngeal infection with internal jugular vein thrombosis, followed by distant infection focus, such as septic pulmonary embolism. The main causative organisms are anaerobic bacteria in the oral cavity, namely Fusobacterium necrophorum . We encountered an extremely rare case of Lemierre's syndrome, where double vision was found to be the first symptom. The patient's blood culture results showed the presence of F. nucleatum, which spread from the sphenoid sinus to the skull base because of chronic sinusitis; the patient presented with longus colli abscess, clivus osteomyelitis, venous thrombosis, and hematogenous infection. Antibiotic treatment with sulbactam/ampicillin was continued for 14 weeks, and no recurrence has been observed so far. Lemierre's syndrome can be complicated with atypical symptoms such as double vision if the cranial nerves are involved. It might be important to consider this disease in the differential diagnosis in the presence of cranial nerve symptoms of unknown origin with fever or inflammatory findings.